Acute Anti-Inflammatory Study by Oral Administration of Cherry Leaf (Muntingia Calabura L.) Infusion in Inflammation-induced Wistar Strain White Rats (Rattus Norvegicus) - Ramadhan, Putra; Rohmawaty, Enny; Rosdianto, Aziiz Mardanarian (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Inflammation is a response of the body’s defense system in preparation for tissue repair. Acute inflammation is characterized by heat, redness, pain, and formation of edema. Acute inflammation involve the realese of inflammatory mediators. Muntingia calabura is a herbal plant commonly used as an anti-inflammatory medicine containing bioactive coumpounds such as flavonoids, triterpenoids, and alkaloids that can inhibit the regulation of inflammatory mediators. This study aims to determine the anti-inflammatory activity and optimal dosage of M. calabura infusion in addressing acute inflammation in rats. The research method is a laboratory experiment using Wistar strain white rats that divided into 7 treatment groups: normal, negative control, positive control (sodium diclofenac and methylprednisolone), and M. calabura infusion at doses of 150, 300, and 600 mg/kg body weight. Each rats model induced with 1% carrageenan at 0.2 ml intraplantar, the formed edema is measured using a plethysmometer every 30 minutes for the first 3 hour and every 60 minutes for the following 3 hour. The result indicate that M. calabura infusion has acute anti-inflammatory effect on white rats model induced with carrageenan, with the most optimal dose being 600 mg/kg body weight, showing a pattern of anti-inflammatory activity similar to methylprednisolone.